Pengaruh penggunaan minyak ikan lemuru, tallow, dan tongkol jagung dalam ransum terhadap kinerja dan komposisi asam lemak daging itik - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
Low fat meat with higher unsaturated fatty acid composition is the requirement of health that need to be filled immediately. Thus, the major purpose of this research was to find out the influence of utilizing lemuru fish oil, tallow and corn cob in rations on the fat content and the fatty acids composition of duck meat. This study used the completely randomized design with 2x2x3 factorial pattern, two kinds of lipide, lemuru fish oil and tallow, two levels of lipide, 0 and 6%, and three levels of corn cob 0%, 10%, and 20%. Each combination of treatments used four replication. The data were analyzed with analysis of variance and Duncan's multiple range test. The result of the research showed that the utilization lemuru fish oil or tallow in ration had not significant influence on the duck performance, but significantly influenced on the contents of arachidonic acid, eicosapentaenoic acid (EPA), and docosahexaenoic acid (DHA). In this case, the utilization of lemuru fish oil could increase the content of three kinds fatty acid of meat duck. Corn cob utilization showed influences on the increase of feed consumption and feed conversion, and decrease of fat consumption, while toward the body weight gain, percentage of carcass and the fat content of meat had not significant influences. The interaction occurred between corn cobs level with the lipids level on the feed consumption, body weight gain, and arachidonic acid contents. The interaction also occurred between the kind of lipid with lipid level on the arachidonic acid, EPA, and DHA.